The complexity of the work of nurses in Primary Health Care - Sandra Rejane Soares Ferreira; Lisiane Andréia Devinar Périco; Vilma Regina Freitas Gonçalves Dias
ABSTRACT Objective: to promote thinking on the work of nurses in Primary Health Care (PHC) and the necessary aspects for the (re)construction of this professional practice, reinforcing its role in the care of individuals, families and communities. Method: to apply the questions raised in the process of organizing a book, the literature and the PHS work experience of the authors. Results: Conflicts, dilemmas and relevant aspects of the practice of nurses in PHC are presented, contributing to critical thinking about the context of work and the need to articulate the category in the construction of its workspace. Final considerations: the practice of nurses in PHC is broad and a process of qualification field, whether performing in clinical, educational or managerial activities, and nurses need to be familiar with these contents in their daily work, seeking to articulate their class entities for the development of this specialty.